2007
DOI: 10.1007/s11746-007-1050-8
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Phytic Acid in Producing Soy Protein Ingredients

Abstract: Phytic acid (myo-inositol hexaphosphate) is present in soybeans and soy protein products at 1-2% dry matter. Phytate causes poor absorption of essential electrolytes and minerals, and binds to proteins and co-precipitates with isoelectric soy protein isolates. We determined how phytic acid partitioned during different procedures to prepare soy protein ingredients. Procedure and soybean variety significantly affected phytic acid content and recovery. High-sucrose/low-stachyose (HS/LS) soybeans contained signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
(38 reference statements)
1
19
0
4
Order By: Relevance
“…For this reason, the preparation of soya protein isolates and concentrates with reduced phytate contents to avoid Zn deficiencies in human infants has been a goal for decades (53) . As discussed by Erdman (54) , protein concentrates with reduced phytate contents can be prepared by exploiting the capacity of phytate to bind protein, which has been demonstrated in soya (55) and rapeseed (56) , and the fate of phytate following the preparation of soya protein concentrates/isolates has been reviewed (57) . In relation to ternary complexes and protein availability, Champagne et al (58) suggested that the protein moiety of ternary complexes is comprised of either amino acids or small peptides and it then follows that the amount of protein bound in ternary complexes in the small intestine may not be sufficient to compromise amino acid digestibility (9) .…”
Section: Ternary Protein -Phytate Complexesmentioning
confidence: 99%
“…For this reason, the preparation of soya protein isolates and concentrates with reduced phytate contents to avoid Zn deficiencies in human infants has been a goal for decades (53) . As discussed by Erdman (54) , protein concentrates with reduced phytate contents can be prepared by exploiting the capacity of phytate to bind protein, which has been demonstrated in soya (55) and rapeseed (56) , and the fate of phytate following the preparation of soya protein concentrates/isolates has been reviewed (57) . In relation to ternary complexes and protein availability, Champagne et al (58) suggested that the protein moiety of ternary complexes is comprised of either amino acids or small peptides and it then follows that the amount of protein bound in ternary complexes in the small intestine may not be sufficient to compromise amino acid digestibility (9) .…”
Section: Ternary Protein -Phytate Complexesmentioning
confidence: 99%
“…de cálcio, de ferro e de zinco, os quais não são prontamente absorvidos. Devido a sua ação quelante, o ácido fítico é considerado fator antinutricional, afetando a biodisponibilidade dos minerais e contribuindo para sua deficiência (DEAK; JOHNSON, 2007;LAZZARI, 2006;AL-WAHSH et al, 2005;SANDBERG, 2002). Estudos sugerem que o fitato tem ação anticarcinogênica em vários tipos de câncer.…”
Section: Introductionunclassified
“…O ácido fítico é encontrado em alimentos altamente carregados negativamente e formam complexos ou ligações com moléculas de cargas positivas, tais como cátions metálicos e proteínas (DEAK; JOHNSON, 2007). Ocorrem diferentes mecanismos para a interação do fitato com a proteína, que depende dos diversos pHs (pH < 5, pH 5 -7 e pH > 7).…”
Section: Introductionunclassified
See 2 more Smart Citations